Allergens derived from shrimp - Packiamuthu Dewaprigam Solomen, Mary Margaret; Selamat, Jinap; Abdull Razis, Ahmad Faizal (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
Allergy caused by food is usually type 1 allergy of four types of allergic reactions. One of the most widespread allergic is those that are caused by crustacean shellfish. Crustaceans are classified among arthropods which include crab, crayfish, lobster, prawn and shrimp. Shrimp which are broadly consumed as nutritional food is one of the most important food that contribute to allergy. Thus, reducing the allergenicity of shrimp allergen will be helpful to individuals who are sensitive to shrimp and for this reason the characteristics of each allergen need to be studied. Those sensitized individuals can develop urticaria, angiodema, laryngospasm, asthma and life threatening anaphylaxis. To date, four main allergens contribute to allergic reactions. They are tropomyosin (TM), a highly conserved and heat stable myofibrillar protein of 35-38 kDa followed by arginine kinase (AK) which is also known as Pen m 2 or Lit v 2 with 40 kDa. Two other contributing allergens are sarcoplasmic calcium-binding protein (SCP) also known as Lit v 4 with 22 kDa and myosin light chain (MLC) which is also termed as Lit v 3 with 20 kDa. This mini-review will provide a better understanding of each allergen derived from shrimp which subsequently will help to reduce the allergenicity.